2005
DOI: 10.1074/jbc.m506700200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Gz in Pancreatic Islet β-Cell Biology

Abstract: Glucose-stimulated insulin secretion and ␤-cell growth are important facets of pancreatic islet ␤-cell biology. As a result, factors that modulate these processes are of great interest for the potential treatment of Type 2 diabetes. Here, we present evidence that the heterotrimeric G protein G z and its effectors, including some previously thought to be confined in expression to neuronal cells, are present in pancreatic ␤-cells, the largest cellular constituent of the islets of Langerhans. Furthermore, signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…Also completely novel was the finding that the PTX-insensitive heterotrimeric G protein Gz mediates the effect. While Gz has not previously been linked to norepinephrine, it is present in the ␤-cell and is activated by PGE 1 (57,58). The probable reason why this effect of norepinephrine has been hidden for so long is that as norepinephrine inhibits exocytosis, there was little need to look for an effect on endocytosis.…”
Section: Norepinephrine Has Two New Tricks and A New G Protein Partnermentioning
confidence: 99%
“…Also completely novel was the finding that the PTX-insensitive heterotrimeric G protein Gz mediates the effect. While Gz has not previously been linked to norepinephrine, it is present in the ␤-cell and is activated by PGE 1 (57,58). The probable reason why this effect of norepinephrine has been hidden for so long is that as norepinephrine inhibits exocytosis, there was little need to look for an effect on endocytosis.…”
Section: Norepinephrine Has Two New Tricks and A New G Protein Partnermentioning
confidence: 99%
“…Immunohistochemical Assays-Tissues were dissected, fixed, and sectioned as previously described (13). For insulin immunostaining, the HistoMouse-MAX kit (Invitrogen) was used with prediluted guinea pig anti-insulin primary antibody (Invitrogen) incubated for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…As expected for a member of the G␣ i subfamily, constitutively activated G␣ z inhibited GSIS from 832/13 cells (13). More importantly, inhibition of insulin secretion by prostaglandin E1 was PTX-insensitive and could be blocked either by overexpression of the "regulator of G protein signaling" domain of RGSZ1, a G␣ z -specific deactivator (15), or by small interfering RNA-mediated knockdown of G␣ z expression (13). Together, these data indicated that endogenous G␣ z in the 832/13 cells coupled to endogenous G proteincoupled receptors to inhibit insulin secretion.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The mechanism involves G βγ blockade of syntaxin binding to SNAP25 , Gerachshenko et al 2005, Photowala et al 2006. Although it was once believed that all physiological inhibitory effects on the β-cells were mediated by the Pertussis toxinsensitive (PTX)-sensitive heterotrimeric G i and G o proteins (Komatsu et al 1995), it has been reported that inhibition of adenylyl cyclase by PGE 1 is mediated via G z (Kimple et al 2005(Kimple et al , 2008. Exocytosis has to be followed by endocytosis to recapture the granule membrane that has been added to the plasma membrane of the cell in order to maintain cellular homeostasis and integrity (Rizzoli & Jahn 2007).…”
Section: Introductionmentioning
confidence: 99%